The Critical Theory of Religion; the Frankfurt School From Universal Pragmatic to Political Theology - Siebert, Rudolf J. (Berlin : De Gruyter, Inc., 2016)
Sinceits founding by Jacques Waardenburg in 1971, Religion and Reason has been a leading forum for contributions on theories, theoretical issues and agendas related to the phenomenon and the study of religion. Topics include (among others) category formation, comparison, ethnophilosophy, hermeneutics, methodology, myth, phenomenology, philosophy of science, scientific atheism, structuralism, and theories of religion. From time to time the series publishes volumes that map the state of the art and the history of the discipline.
Intro; Dedication; Acknowledgement; Table of Contents; Introduction; Chapter I. Theory of Communicative Praxis; Chapter II. Critical Theory of Religion; Chapter III. Critical Political Theology; Notes; Index of Authors; Bibliography
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 050, 082, 650
Keywords: RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Religion -- Philosophy -- History -- 20th century; Sociology -- Philosophy -- History -- 20th century; Communication -- Philosophy -- History -- 20th century; Frankfurt school of sociology; Religion -- Philosophy; Electronic books